PROMOSI KESELAMATAN DAN KESEHATAN KERJA DI INDUSTRI INFORMAL KRIPIK SINGKONG TAHUN 2021 - Adini Anggun Risanti Putri; Friska Ayu (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
In 2003, 3.2% of the total United States workforce lost productive time due to low back pain (Colorodo Department of Public Health and Environmental Occupational Health, 2012).Occupational Health and Safety (K3), namely to create a safe and secure work environment for workers or employees in the industry concerned, this industry has potential hazards to health, one of which is Low Back Pain (LBP) is a very serious world health problem. In general, it can cause activity restrictions as well as absenteeism from work, commonly felt low back pain. UD. Barokah is a cassava chips industry in Mojokerto. In this research method using pretest and posttest, video counseling about Low Back Pain. The results of the research that were obtained before seeing the counseling video had understood about Low Back Pain by answering the pretest questions, there were 3 respondents (20%). The second did a posttest after seeing the counseling video, they understood about Low Back Pain by answering the posttest questions of 9 respondents (60%). Keywords: Low Back Pain, Occupational Health and Safety, Cassava Chips.